Nearly all single base substitutions in DNA fragments joined to a GC-clamp can be detected by denaturing gradient gel electrophoresis. - Myers, R M (1985)
Duplex DNA fragments differing by single base substitutions can be separated by electrophoresis in denaturing gradient polyacrylamide gels, but only substitutions in a restricted part of the molecule lead to a separation (1). In an effort to circumvent this problem, we demonstrated that the melting properties and electrophoretic behavior of a 135 base pair DNA fragment containing a beta-globin promoter are changed by attaching a GC-rich sequence, called a 'GC-clamp' (2). We predicted that these changes should make it possible to resolve most, if not all, single base substitutions within fragments attached to the clamp. To test this possibility we examined the effect of several different single base substitutions on the electrophoretic behavior of the beta-globin promoter fragment in denaturing gradient gels. We find that the GC-clamp allows the separation of fragments containing substitutions throughout the promoter fragment. Many of these substitutions do not lead to a separation when the fragment is not attached to the clamp. Theoretical calculations and analysis of a large number of different mutations indicate that approximately 95% of all possible single base substitutions should be separable when attached to a GC-clamp.